Peripheral brain-derived neurotrophic factor (BDNF) as a biomarker for affective disorders? - Gass, Peter; Hellweg, Rainer (The international journal of neuropsychopharmacology, 2010)
After more than a decade of ‘a molecular and cellular theory of depression’ the neurotrophin brain-derived neurotrophic factor (BDNF) remains a central part of the concept for the pathophysiology of depression and antidepressant treatment (Altar, 1999; Duman et al.1997). Stress, an important precipitant of depression, reduces the expression of BDNF, especially in the hippocampus, while a plethora of antidepressant measures, e.g. antidepressant drugs, electroconvulsive treatment and also environmental enrichment, increase BDNF expression (Krishnan & Nestler, 2008; Martinowich et al.2007). Thus, BDNF could be a valuable biomarker for a depressive state and the recovery from it. Unfortunately, CSF levels of BDNF are already at the limit of detection in healthy individuals, despite sensitive methods of analysis (Burbach et al.2004). Of course it is also not possible to easily determine BDNF brain tissue levels in the living patient. Therefore, there is great interest in peripheral measures of humoral BDNF, particularly in blood (Brunoni et al.2008; Sen et al.2008).